2021
DOI: 10.1186/s12984-021-00957-6
|View full text |Cite
|
Sign up to set email alerts
|

A novel upper-limb tracking system in a virtual environment for stroke rehabilitation

Abstract: Background The transfer of the behaviors of a human’s upper limbs to an avatar is widely used in the field of virtual reality rehabilitation. To perform the transfer, movement tracking technology is required. Traditionally, wearable tracking devices are used for tracking; however, these devices are expensive and cumbersome. Recently, non-wearable upper-limb tracking solutions have been proposed, which are less expensive and more comfortable. However, most products cannot track the upper limbs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 37 publications
0
17
0
1
Order By: Relevance
“…Nine studies describing the use of sensors for remote monitoring or rehabilitation were identified in stroke patients. Four studies utilized sensors in rehabilitation which resulted in improvement in upper limb function [ 11 , 12 , 13 , 14 ], Lee YM et al used sensors to measure upper limb impairment and disability [ 15 ] and Song Y et al used sensors for both stroke prevention and rehabilitation nursing via a mobile medical management system based on Internet-Of-Things technology [ 16 ]. Chen SC et al demonstrated superior or equal efficiency of a Microsoft Kinect-based exergaming telerehabilitation system compared to conventional one-on-one physiotherapy in chronic stroke patients [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nine studies describing the use of sensors for remote monitoring or rehabilitation were identified in stroke patients. Four studies utilized sensors in rehabilitation which resulted in improvement in upper limb function [ 11 , 12 , 13 , 14 ], Lee YM et al used sensors to measure upper limb impairment and disability [ 15 ] and Song Y et al used sensors for both stroke prevention and rehabilitation nursing via a mobile medical management system based on Internet-Of-Things technology [ 16 ]. Chen SC et al demonstrated superior or equal efficiency of a Microsoft Kinect-based exergaming telerehabilitation system compared to conventional one-on-one physiotherapy in chronic stroke patients [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2 illustrates the statistical summary of all sixteen papers included in this review. As for publication years, one study was published in 2018 [ 23 ], three in 2019 [ 19 , 25 , 26 ], five in 2020 [ 11 , 14 , 20 , 21 , 24 ], four in 2021 [ 12 , 13 , 14 , 15 ], and three up till September 2022 [ 16 , 18 , 22 ]. The increased number of publications made since 2020 during the recent COVID-19 pandemic may reflect the growing interest in remote rehabilitation technology in neurological diseases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Conventional physiotherapy, including cryotherapy, exercise balls, manual therapy, and electrotherapy, remains a common practice in the physiotherapy profession [2]. With the recent upgradation in modern science, technology, and healthcare delving into each other, virtual and augmented reality have become integrated parts of rehabilitation programs for musculoskeletal and neurological conditions [3]. Gamification is a novel interventional approach to functional recovery and rehabilitation by employing elements of games in the process of rehabilitation by using a goal-oriented, 3-D immersive gaming interface approach.…”
Section: Introductionmentioning
confidence: 99%